2021
DOI: 10.2147/cia.s314689
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and Other Competing Causes of Death in Male Breast Cancer Patients: A Population-Based Epidemiologic Study

Abstract: Purpose: Male breast cancer (MBC) is a rare disease that tends to occur in elderly men.Little is known about the causes of death in MBC because of the small sample size of most studies. This study aimed to investigate the causes of death in MBC patients. Patients and Methods: MBC patient data were obtained from the Surveillance, Epidemiology, and End Results database . Time trends of MBC mortality in the US population were analyzed using Joinpoint software. We calculated the proportion of each cause of death i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Neither study adequately accounted for competing risks and resulted in biased conclusions, while our competing risk model provided a more reliable framework to analyze the interaction between BC and CVD, as it correctly estimated the marginal probability of an event in the presence of competing events [ 26 ]. Further supporting evidence comes from another study using the competing risk model that found that the risk of CVD-related death is higher than cancer-related death in older patients with early-stage breast cancer [ 32 ]. Interestingly, aging is a well-known risk factor for CVD and cancer, but current guidelines remain controversial about defining the age cutoff for high-risk CVD death in cancer patients.…”
Section: Discussionmentioning
confidence: 98%
“…Neither study adequately accounted for competing risks and resulted in biased conclusions, while our competing risk model provided a more reliable framework to analyze the interaction between BC and CVD, as it correctly estimated the marginal probability of an event in the presence of competing events [ 26 ]. Further supporting evidence comes from another study using the competing risk model that found that the risk of CVD-related death is higher than cancer-related death in older patients with early-stage breast cancer [ 32 ]. Interestingly, aging is a well-known risk factor for CVD and cancer, but current guidelines remain controversial about defining the age cutoff for high-risk CVD death in cancer patients.…”
Section: Discussionmentioning
confidence: 98%
“…Although we were not able to run a survival analysis due to the small sample size, we noted that one out of the four patients who died, died from non-breast cancerrelated causes, while three died due to metastatic disease. While the survival rate for male and female breast cancer is similar, male patients are more likely to die from non-breast cancer-related causes (22). This may be explained by their older age at diagnosis and increased cardiovascular comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al, in their SEER-based analysis of 6426 MBCs in period 1975-2016, observed that among all the MBCs who died, 42.75% died of breast cancer and 57.3% died of nonbreast cancer causes including cardiovascular disease (CVD) (26.9%), other cancers, and nervous system disease. CVD as the cause of death was more common than breast cancer in age >75 years [29]. 4 International Journal of Breast Cancer…”
Section: Treatment Treatment Of Localised Invasive Early Mbc Usually ...mentioning
confidence: 99%